ANTI-COMMONS IN THE AQUACULTURE SECTOR IN PORTUGAL: ENTREPRENEURSHIP AND BUREAUCRACY - Coelho, Manuel; Ferreira, Manuel Alberto (Acta Scientiae et Intellectus, 2024)
Last decades of the 20th century have shown many problems arisen from the emergence of commons mismanagement and under-defined property rights (The “Tragedy of the Commons”, cf. Hardin, 1968), affecting, especially, the design of environmental and natural resources management policy. In the 80s, Michelman introduced another problem, this time about the excessive fragmentation of property rights. A new concept, “anticommons”, was developed to put in evidence some problems one can see as the mirror image of traditional “Tragedy of the commons”. These problems include the under-use of resources and may come from several sources, including bureaucracy. Michelman introduced the concept of “anticommons” to explain “a type of property in which everyone always has rights respecting the objects in the regime, and no one, consequently, is ever privileged to use any of them except as particularly authorized by others”. In this sense, “anticommons” is seen as a property regime in which multiple owners hold effective rights of exclusion in a scarce resource. The problem stands in this: coexistence of multiple exclusion rights creates conditions for suboptimal use of the common resource. Buchanan and Yoon (2000) suggested a special view of this problem. The authors stated that the anti-commons construction offers an analytical tool for isolating a central feature of “sometimes disparate institutional structures”. This means that the inefficiencies introduced by overlapping and intrusive regulatory bureaucracies may be studied with the help of this conceptualization. When an entrepreneur seeks to invest in a project and his action is inhibited by the necessity of getting permits from several national and regional agencies, each one holding exclusion rights to the project, we may face the “Tragedy of the Anticommons”. In this context, the possible emergence of a situation of anticommons can create a lot of problems in the development of local initiatives of entrepreneurship, affecting the potential of innovation and of regional development. The problem stands in this: coexistence of multiple exclusion rights creates conditions for suboptimal use of the common resource. Buchanan and Yoon (2000) suggested a special view of this problem. The authors stated that the anti-commons construction offers an analytical tool for isolating a central feature of “sometimes disparate institutional structures”. This means that the inefficiencies introduced by overlapping and intrusive regulatory bureaucracies may be studied with the help of this conceptualization. When an entrepreneur seeks to invest in a project and his action is inhibited by the necessity of getting permits from several national and regional agencies, each one holding exclusion rights to the project, we may face the “Tragedy of the Anticommons”. In this context, the possible emergence of a situation of anticommons can create a lot of problems in the development of local initiatives of entrepreneurship, affecting the potential of innovation and of regional development.